Contextual advertising as an Internet marketing tool - CHERNYSH Тетяна; SALIMON Ольга (Commodity science. Technologies. Engineering, 2023)
Contextual advertising is a progressive online marketing tool that allows you to attract new customers, expand the market, increase brand awareness, boost your revenues and profitability. The use of online advertising tools should be approached in a differentiated manner, in accordance with the tasks that a business sets itself in a particular market and under certain conditions. That is why contextual advertising is a very relevant tool for promoting business on the Internet in the period of post-war market recovery. The article aims at highlighting the importance of using contextual advertising as an effective tool for business promotion and at determining the prospects for the development of contextual advertising in the Ukrainian market in the post-war period. The study was conducted using the following methods: data analysis, synthesis and logical generalisation of results; systemic, structural and statistical analysis with the use of graphical methods. The main sources of information were scientific papers related to online advertising, marketing research publications, expert blogs of professionals in the field of contextual advertising, and official statistical information from Internet resources. Contextual advertising is considered as one of the most widespread Internet marketing tools, its advantages and disadvantages are highlighted. Different models of payment for contextual and targeted advertising are analysed, namely: Cost-Per-Click, Count-Per-Mile, Cost-Per-Action, Cost-Per-Engagement, Cost-Per-View, Cost-Per-Install, which play an important role in promoting goods and services via the Internet. The prospects for the development of contextual advertising in Ukraine in the post-war period are justified, which will contribute to the promotion of goods and services in the market, the improvement of the image of brands, and therefore, the increase of recognition among the target audience. It was determined that contextual advertising, compared to other types of advertising, is relatively new, and its ability to be present in various search engines, on partner sites, in social networks or in mobile applications makes it a powerful tool for Internet marketing in the post-war period. A promising area for further research is the study of the development of cross-platform capabilities of contextual advertising in the context of integration with new technologies, such as augmented and virtual reality and voice assistants.